Notch Signaling in Macrophages in the Context of Cancer Immunity - Palaga, Tanapat; Wongchana, Wipawee; Kueanjinda, Patipark (Frontiers in Immunology, 2018)
Macrophages play both tumor-suppressing and tumor-promoting roles depending on the microenvironment. Tumor-associated macrophages (TAMs) are often associated with poor prognosis in most but not all cancer. Understanding how macrophages become TAMs and how TAMs interact with tumor cells and shape the outcome of cancer is one of the key areas of interest in cancer therapy research. Notch signaling is involved in macrophage activation and its effector functions. Notch signaling has been indicated to play roles in the regulation of macrophage activation in pro-inflammatory and wound-healing processes. Recent evidence points to the involvement of canonical Notch signaling in the differentiation of TAMs in a breast cancer model. On the other hand, hyperactivation of Notch signaling specifically in macrophages in tumors mass has been shown to suppress tumor growth in an animal model of cancer. Investigations into how Notch signaling is regulated in TAMs and translates into pro- or anti-tumor functions are still largely in their infancy. Therefore, in this review, we summarize the current understanding of the conflicting roles of Notch signaling in regulating the effector function of macrophages and the involvement of Notch signaling in TAM differentiation and function. Furthermore, how Notch signaling in TAMs affects the tumor microenvironment is reviewed. Finally, the direct or indirect cross-talk among TAMs, tumor cells and other cells in the tumor microenvironment via Notch signaling is discussed along with the possibility of its clinical application. Investigations into Notch signaling in macrophages may lead to a more effective way for immune intervention in the treatment of cancer in the future.